The Indigenous Ecotourism in Kajang South Sulawesi: Empowerment Issues in The Context of Pa'pasang Ri Kajang - Ega Rusanti; Andi Syathir Sofyan; Syarifuddin Syarifuddin; Akramunnas Akramunnas (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
The issue of empowerment in indigenous groups has very little attention. This discussion is critical because empowering the indigenous people of Kajang results from a tourism visit that collided with Pa'pasang ri Kajang’s value. This article bridges the relationship of ecotourism with the values of the Kajang tribe's beliefs. Second, investigating the issue of empowerment of the Kajang Indigenous community that hinders the development of ecotourism. This article uses ethnographic research methods. The data comes from direct interviews with the Ammatoa indigenous people. The Pa'pasang ri Kajang philosophy plays an essential role in the Kajang community's daily activities; however, various problems arise to develop ecotourism. What the Kajang community should get is feedback from tourist visits. Of course, this article provides knowledge implications about travelling to indigenous peoples' areas and providing input to stakeholders to develop ecotourism.